Insights into the U1 small nuclear ribonucleoprotein complex superfamily - Guiro, J; O'Reilly, D (Wiley, 2014)
The 164 bp U1 small nuclear (sn) RNA is one of the most abundant noncoding (nc) RNA in human cells, estimated to be in the region of 106 copies/cell. Although best known for its role in pre-messenger RNA (mRNA) splicing events, research over the past 20 years has revealed diverse functions of this ncRNA in mammalian cell types. Excellent reviews exist detailing the role of U1 snRNA in pre-mRNA splicing events. This review highlights what is currently known regarding the additional roles, snRNP composition, expression profiles, and the genomic organization of this ncRNA.